Scientometrical Analysis On The Use Of Cost Information In Decision Making By Using Managirieal Accounting Cocept - Alnujaimi Aws Saeed Mirdan (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
From simple analytical cost accounting, it has now reached an integrated system to meet the needs of managers regarding the measurement of enterprise performance and the need to make the best decisions. The field of using costs in decision-making has become multifunctional and has expanded into all branches of activity, including non-productive ones. The purpose of this research is to see how motivated are the concerns of research in the academic world related to the field of costs and their usefulness in decision-making based on scientometric analysis with the help of two software tools, namely OpenAlex and VoSviewer. From the scientometric analysis undertaken, the conclusion emerges that research in the field of the use of costs in decision-making developed rapidly after 2014, with the number of journals in the economic field doubling between 2015-2024. However, there is an interconnection between the terms of one cluster and the terms of another cluster, which demonstrates the fact that the issue of costs and decisions cannot be reduced only to the field of management accounting, it requires a holistic vision and cooperation between various fields, the basis remaining however, the level of the economic field.